2020
DOI: 10.1371/journal.pone.0237383
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of serum drug monitoring complementing urine analysis to assess adherence to antihypertensive drugs in first-line therapy

Abstract: With obesity having doubled in the last decade, hypertension is on the rise. In one-third of hypertensive patients the metabolic syndrome is present. This might be one factor for the increasing number of prescriptions for angiotensin receptor blockers and calcium-channel blockers besides a more favorable risk-to-benefit ratio. The aim of the present study was to evaluate a therapeutic drug monitoring (TDM) method for assessment of adherence based on cutoffs in inpatients and to compare it to an established uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Assessing adherence based on serum drug concentrations to complement urine analysis is expected to be more accurate than urine analysis alone, particularly when using the so-called dose-related concentration approach as proposed, e.g., by Ritscher et al [ 24 ]. In general, drugs with low bioavailability, low renal excretion, or underlying extensive metabolism may be underestimated concerning their adherence when using qualitative urine analysis alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing adherence based on serum drug concentrations to complement urine analysis is expected to be more accurate than urine analysis alone, particularly when using the so-called dose-related concentration approach as proposed, e.g., by Ritscher et al [ 24 ]. In general, drugs with low bioavailability, low renal excretion, or underlying extensive metabolism may be underestimated concerning their adherence when using qualitative urine analysis alone.…”
Section: Resultsmentioning
confidence: 99%
“…So far and to the best of our knowledge, no research article demonstrating the feasibility of VAMS for adherence monitoring was published. Therefore, the aim of this study was to develop and evaluate a VAMS-based strategy for adherence monitoring of antipsychotics in FPB by using drug concentrations to complement qualitative urine analysis [ 24 ]. Analysis should be done by means of LC-HRMS/MS and the whole quantitative workflow should be validated in accordance with international guidelines [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we controlled for creatinine levels to minimise potential confounder variables such as fluid consumption and age. Another possible explanation is based on the generalised assumption that increased serum metabolite concentration will result in increased urine metabolite excretion ( Ritscher et al., 2020 ). However, while this may hold true for healthy individuals, in the context of MS or an alternative disease state, the possible incapacity to excrete these inflammatory mediators as efficiently as healthy individuals, may have resulted in these findings.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gupta et al demonstrated that liquid chromatography-mass spectrometry (LC-MS)-based analyses of urine or blood of non-adherent patients improve their adherence with consecutive meaningful reductions in blood pressure [10]. Hereby, assessing adherence based on blood concentrations with individually calculated lower dose-related concentrations (DRC) is more accurate than using qualitative analysis alone [11,12]. Up to date, several LC-MS methods for the quantification of AHD exist [13][14][15][16] but they are based on blood, plasma, or serum needing venipuncture, which can cause discomfort and anxiety and requires healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%